Citrate Metabolism in Aerobacter cloacae - O'Brien, R. W. (1974)
Growth of Aerobacter cloacae on citrate either anaerobically or aerobically did not require and was not stimulated by the presence of Na(+) in the medium. Citrate was metabolized anaerobically via the fermentation pathway as evidenced by the (i) presence of oxalacetate decarboxylase, (ii) induction of citrate lyase, and (iii) repression of α-ketoglutarate dehydrogenase under anaerobic conditions. Thus, although all the other enzymes of the citric acid cycle were present in anaerobic cells, this pathway was not available for the metabolism of citrate. Citrate was metabolized aerobically via the citric acid cycle, since (i) citrate lyase but not oxalacetate decarboxylase was repressed and (ii) α-ketoglutarate dehydrogenase was induced under these conditions. The presence of Na(+) in the medium did not lead to a repression of α-ketoglutarate dehydrogenase as in the case of Aerobacter aerogenes. The oxalacetate decarboxylase was a soluble, constitutive enzyme, not activated by Na(+) nor inhibited by avidin. It was slightly inhibited by ethylenediaminetetraacetate but was not stimulated by Mg(2+) or Mn(2+). Thus, this enzyme differed markedly in its properties from the same enzyme found in citrate-grown A. aerogenes.